An Overlooked but Effective Wound Care Methodology: Hydromechanical Therapy Revisited. Issue 8 (August 2018) - Desjardins, Haley; Guo, Lifei
Abstract : Summary: Chronic wounds are frequently difficult, expensive to treat, and pose a significant burden on both the patient's quality of life and health care system. Their recalcitrance to treatment stems from multiple factors, particularly the presence of bacterial biofilms within the wound bed. However, a commonly overlooked modality in the field of wound care, pressurized irrigation, offers an inexpensive mechanical debridement force capable of dislodging these biofilms that contribute to delayed healing of chronic wounds. We present here a single clinical case of a difficult nonhealing wound that had previously failed 3 months of negative-pressure wound therapy, a much more expensive modality. This chronic plantar foot wound was treated with daily application of hydromechanical therapy using tap water at home. It achieved a stable granulation surface, and with a small skin graft, healing with no recurrence seen at 15-month follow-up. We speculate that a combination of tissue stimulation and disruption of the wound surface biofilm contribute to improved healing, supporting a reevaluation for the use of pressurized irrigation in the treatment of chronic wounds.